ATHLETIQUE: interest of an adapted physical activity program in patients with juvenile idiopathic arthritis: a feasibility and preliminary effectiveness study - Py, Stéphanie; Maylié, Florine; Parmentier, Anne-Laure; Vidal, Chrystelle; Cuinet, Benjamin; Mauny, Fréderic; Lohse, Anne; Toussirot, Eric; Yoshimasa, Sagawa; Tordi, Nicolas; Binda, Delphine; Ballot-Schmit, Claire (Frontiers in Immunology, 2023)
Background Juvenile Idiopathic Arthritis (JIA) is associated with joint inflammation, pain and limited joint mobility, impacting the practice of physical activities. Adapted Physical Activities (APA) are an increasingly used method of rehabilitation, but additional studies are needed to define the nature of the most appropriate physical activity for patients with JIA. The “ATHLETIQUE” project aims to evaluate the impact of a program integrating APA sessions with use of a pedometer watch, on disease activity in patients with JIA. Methods This study will be a randomized, multicenter, open-label, controlled clinical trial with 2 parallel arms. The patients included in this study will be children and adolescents with JIA, aged 6 to 17 years. The experimental group (30 patients) will participate in an APA program for 3 months and will use a pedometer watch for one year. We will evaluate and compare the change in disease activity measurements (primary objective), fatigue, pain, quality of life, level of physical activity, functional capacities, and muscle strength (secondary objectives) after 14, 26 and 50 weeks. The control group (10 patients) will undergo the same evaluations as the experimental group but will not participate in the APA program and will not wear the pedometer watch. Expected results The APA program may help to promote an active lifestyle with regular physical activity, preventing comorbidities and motor disability. Promising results on disease activity, functional capacities and quality of life would enable us to envisage a larger research program with a view to optimizing and assessing APA for children with JIA. Discussion This study will be conducted in the short and medium-term, with one-year follow-up, including 3 months of APA sessions for the experimental group. The sessions proposed during the APA program will mainly be aerobic and bodyweight exercises. Furthermore, in contrast to previous studies on this topic, our study will integrate a novel element, namely the use of a pedometer watch. This watch will help to implement strategies to address motivation. This study aims to improve physical and mental well-being, provide a basis for the design of a larger study, and propose recommendations adapted to children with JIA. Trial registration Registered with ClinicalTrials.gov under the number NCT05572424